GAMBARAN TINGKAT PENGETAHUAN IBU TENTANG IMUNISASI DASAR DI PUSKESMAS LIMAPULUH - Siska Dwi Lestari; Erika Erika; Wasisto Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Immunization is an attempt to increase a person's immunity to a disease. The provision of basic immunization is a public health effort that has proven effective and has a positive impact. Basic immunization is a routine immunization that must be given on a schedule consisting of hepatitis B, BCG, DPT, polio and measles immunizations. Knowledge is information that can change a person and become a basis for action. So that knowledge is able to provide a person's ability to take a more effective action. A high level of knowledge can influence a person to become more aware of what is the responsibility such as meeting the needs of the child, namely by immunizing the child according to a predetermined schedule. This research is a quantitative research with a descriptive method. The sample used in this study was 91 people with purposive sampling technique. The univariate test results showed that the majority of respondents were in the age range of 30-39 years as many as 59 people (64,8%), the last high school education as many as 38 people (41,8%), unemployed as many as 77 people (84,6%), Muslims as many as 78 people (85,7%) and children in the range of 1 year as many as 64 people (70,3%). Based on the results of this study, the frequency of maternal knowledge levels about basic immunization was mostly 50 people (54,9%), enough as many as 28 people (30,8%) and minority less as many as 13 people (14,3%).Keywords : immunization; level of knowledge; mother.